Immunostimulatory therapy of frequent respiratory infections in children - E. M. Ovsyannikova; T. Y. Stoyko; M. B. Shabat; N. A. Korovina (Медицинский совет, 2015)
Acute respiratory infections (ARI) are associated with high risk of complications and account for the highest percentage in pediatric morbidity. ARVI complications are usually caused by bacteria. The multimodal treatment should include etiotropic, symptomatic and immunomodulatory therapy. Immunomodulatory therapy has an important role during the acute phase of the disease, as well as in the convalescent period of acute respiratory disease.